Compartments, wingless and engrailed: patterning the ventral epidermis of Drosophila embryos. - Lawrence, P.A.; Sanson, B.; Vincent, J.P. (Development, 1996)
Recent experiments on the wing disc of Drosophila have shown that cells at the interface between the anterior and posterior compartments drive pattern formation by becoming the source of a morphogen. Here we ask whether this model applies to the ventral embryonic epidermis. First, we show that interfaces between posterior (engrailed ON) and anterior (engrailed OFF) cells are required for pattern formation. Second, we provide evidence that Wingless could play the role of the morphogen, at least within part of the segmental pattern. We looked at the cuticular structures that develop after different levels of uniform Wingless activity are added back to unsegmented embryos (wingless- engrailed-). Because it is rich in landmarks, the T1 segment is a good region to analyse. There, we find that the cuticle formed depends on the amount of added Wingless activity. For example, a high concentration of Wingless gives the cuticle elements normally found near the top of the presumed gradient. Unsegmented embryos are much shorter than wild type. If Wingless activity is added in stripes, the embryos are longer than if it is added uniformly. We suggest that the Wingless gradient landscape affects the size of the embryo, so that steep slopes would allow cells to survive and divide, while an even distribution of morphogen would promote cell death. Supporting the hypothesis that Wingless acts as a morphogen, we find that these stripes affect, at a distance, the type of cuticle formed and the planar polarity of the cells.